2020
DOI: 10.1007/978-3-030-46463-9_5
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Self-efficacy

Abstract: Based on studies, the degree of self-efficacy appears to have a strong relationship with positive indicators of employees, such as their well-being, work engagement, and achievements. Other positive indicators of self-efficacy have also been observed, such as the positive effects on well-being and negative effects on burnout. Self-efficacy was described by the originator of the concept, Bandura, as the belief in one's own ability to complete a particular task in a particular situation. It concerns the belief i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
2

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 2 publications
0
2
0
2
Order By: Relevance
“…This is not always true as all efficacious students do not have the tendency to excel in their performance. This perception is drawn from a manuscript that states that practice is also required to achieve good and sustainable performance ( 23 ). Based on this supposition, it can't be claimed right away that students' SE will always impact the students' performance.…”
Section: Theoretical Supportmentioning
confidence: 99%
“…This is not always true as all efficacious students do not have the tendency to excel in their performance. This perception is drawn from a manuscript that states that practice is also required to achieve good and sustainable performance ( 23 ). Based on this supposition, it can't be claimed right away that students' SE will always impact the students' performance.…”
Section: Theoretical Supportmentioning
confidence: 99%
“…Efikasi diri (self-efficacy) adalah keyakinan bahwa seseorang dapat menguasai suatu situasi dan menghasilkan luaran yang positif [3]. Efikasi diri merupakan salah satu aspek pengetahuan tentang diri atau self-knowledge yang paling berpengaruh dalam kehidupan induvidu sehari-hari.…”
Section: Pendahuluanunclassified
“…Hasil analisis menunjukkan indeks separasi responden adalah 2.38 dan indeks separasi item adalah 3,73. Semakin besar nilai pembeda maka kualitas instrumen secara keseluruhan subjek penelitian dan item semakin baik karena mampu mengidentifikasi kelompok responden dan item [3]. Jika dilihat lebih detail dengan menggunakan persamaan pemisahan strata (H), maka untuk subjek H = 3,50 (dibulatkan jadi 3) dan untuk item H = 5,30 (dibulatkan jadi 5).…”
Section: Gambar 3 Fungsi Informasi Pengukuranunclassified
“…Vagni et al (2020) found that individual efficacy in resolving negative feelings and thoughts is a protective strategy against stress and secondary trauma among healthcare and emergency personnel treating COVID-19 in Italy. SFE is associated with a variety of significant concepts, including self-control (G. Zhang et al, 2019), well-being (Kodden, 2020), and work engagement (Burić and Macuka, 2018). Yakın and Erdil (2012) discovered that employee SFE considerably affects work engagement.…”
Section: Self-efficacy and Work Engagementmentioning
confidence: 99%